Trimethoprim / sulfamethoxazole in the treatment of gynecological infections - Valdivia Ponce, Eduardo (2015)
We conducted a study with 80 patients ginecópatas, mortadores of infection problems. Of these, 60 were treated with a new drug trimethoprim + sulfamethoxazole association and comparatively 10 patients with ampicillin and tetracycline 10 others. In the 60 patients studied with trimethoprim-sulfamethoxazole (TMP / SMX) association is summarized as follows: The finding was between 4 and 58 years old. The group of women aged 20-40 years accounted for 54% of gynecological infections. 44.4% of infections were caused by Escherichia coli, Staphylococcus aureus coagulase corresponding to 24% positive infections. The E. coli / staphylococcus aureus association was found with some frequency. Vaginitis and vulvovaginitis were prevailing clinical infections (59%). Except for a few cases, particularly mixed infections, the standard treatment for 7 days with the association trimethoprim + sulfamethoxazole, they produced satisfactory results with clinical and bacteriological cure nearly 100%.